The construct validity of self-regulated learning questionnaire for senior high school students: a Rasch model analysis - Rahmi Ramadhani; Edi Syahputra; Elmanani Simamora (International Journal of Evaluation and Research in Education (IJERE), 2024)
Self-regulated learning (SLR) is a condition in which students actively participate in the process of acquiring knowledge, and it closely relates to students’ metacognitive, motivational, and behavioral aspects. In order to measure this variable, an instrument was developed by referring to the Zimmerman cycle in the form of a questionnaire. Therefore, this study aims to analyze the construct validity of SLR questionnaires designed for high school students through Rasch model analysis. The method employed was descriptive quantitative research. The analyzed questionnaire consists of 50 positive statements, rated on 4-point Likert scale, and arranged of forethought, performance, and self-reflection phases. Furthermore, the construct validity was conducted on 235 third grade (XII) high school students in Gunungsitoli City (Indonesia), with a gender distribution of 58.29% female and 41.70% male. The results showed that the questionnaire with 4-rating scales satisfied the criteria for validity, gender inclusiveness, and unidimensionality based on Rasch model analysis for 25 statements. The implication of this research shows that the SLR questionnaire developed is valid and can be used in wider field research, especially in mathematics learning.